Strategi Pendekatan Sainstifik Learning dalam Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Kelas VI Pada Mata Pelajaran Al-Qur’an Hadits di Madrasah Ibtidaiyah (MI) As Sidiqiyah Kecamatan Siak - Wijiaya, Ridwan Hadi; Anshori, Masum; Risnawati, Risnawati (JURNAL PENDIDIKAN ROKANIA, 2024)
By utilizing the Scientific Learning approach in an effort to enhance the critical thinking skills of students at As Sidiqiyah Islamic Elementary School, Siak District, this research aims to achieve that objective. The research method employed is qualitative, specifically descriptive research. The evaluation of the implementation of the Scientific Learning teaching strategy in improving students' critical thinking abilities in the subject of Al-Qur’an and Hadits yielded satisfactory results. This is evident from the observation of learning outcomes and activities conducted. The improvement in students' critical thinking skills when applying the Scientific Learning teaching strategy reached a percentage of 85%, categorized as good. The students' critical thinking abilities were also assessed as good. Supporting factors in this research involve students' curiosity, self-confidence levels, opportunities, time, and the selection of effective teaching strategies. On the other hand, inhibiting factors include a lack of students' curiosity, low self-confidence levels, time constraints, and the selection of teaching strategies that do not align with the students' needs.